Identities in transitio n the pursuit of Isa. 52:13-53:12 - Joachimsen, Kristin. (Vetus Testamentum, Supplements, 2011)
Isa. 52:13-53:12 has occupied a special position within Jewish and Christian traditions, as well as within biblical scholarship. This book focuses particularly on different ways of reading this text. Historical-critical readings in the tradition after Bernhard Duhm are challenged. In Duhmian readings of Isa. 52:13-53:12, Gottesknecht has become a technical term, Ebed-Jahwe-Lied a genre, Stellvertretung an established theological concept and "servant song research" a separate discipline within biblical scholarship. After a critical presentation of the Duhmian readings, three other ways of reading Isa. 52:13-53:12 based on variations of linguistic theory are presented: one linguistic, one narratological and one intertextual. These show in different manners how the text is unstable, heterogeneous and composite. In these readings, the trope of personification is central.